生命早期饥荒暴露与晚年代谢综合征风险之间的关联 - Yi Zhang; Hongyan Qi; Chunyan Hu; Shuangyuan Wang; Yuanyue Zhu; Hong Lin; Lin Lin; Jie Zhang; Tiange Wang; Zhiyun Zhao; Mian Li; Yu Xu; et al. (Journal of Diabetes, 2022)
Abstract Background Previous studies reported that famine exposure had an effect on metabolic syndrome (MetS). However, there is an inadequacy of study regarding the association between famine exposure, adulthood general obesity, and the risk of MetS. Methods A total of 8883 subjects aged ≥40 years from Jiading community in Shanghai were included. We defined famine exposure subgroups as nonexposed (1963–1974), fetal exposed (1959–1962), childhood exposed (1949–1958), and adolescence exposed (1941–1948). MetS was defined based on the National Cholesterol Education Program Adult Treatment Panel III (NCEP‐ATP III) criteria. Results Compared with the nonexposed group, the risks of MetS were increased in the fetal‐, childhood‐, and adolescence‐exposed groups with odds ratios (OR) and 95% confidence intervals (CI) of 1.48 (1.23–1.78), 1.89 (1.63–2.20), and 2.34 (1.99–2.74), respectively. After adjusting for sex, age, smoking status, drinking status, education, body mass index (BMI), and physical activity, the increased risk of MetS related to the fetal‐exposed and childhood‐exposed groups with OR and 95% CI of 1.42 (1.04–1.94) and 1.50 (1.02–2.21), respectively, were observed only in women. Famine exposure was significantly associated with MetS among individuals with a BMI < 23 kg/m2 (p for interaction between BMI categories and famine exposure = 0.0002 in the whole cohort), while there existed a gender difference (p = 0.0023 in females, p = 0.4484 in males). When evaluating the joint effects of the combination of famine exposure in early life and general obesity in adulthood on MetS, we observed the highest estimate in participants with both adulthood general obesity and fetal famine exposure (OR 17.52; 95% CI, 10.07–30.48) compared with those without famine exposure nor adulthood obesity. Conclusions Obesity in adulthood significantly further aggravated the risk of MetS in individuals who experienced early life undernutrition, especially in females.